MENINGKATKAN KEMAMPUAN MOTORIK HALUS MELALUI KEGIATAN MENGANYAM DENGAN KERTAS BERWARNA ANAK USIA 4-5 TAHUN DI PAUD DARUSSALAMAH DESA PETAPAHAN JAYA KECAMATAN TAPUNG KABUPATEN KAMPAR - Sari, Mila; Zulirfan, Zulirfan; Risma, Devi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine the increase fine motor skills in children aged 4-5 years through weaving activities in early childhood Darussalam Petapahan Jaya Village District Tapung Regency Kampar. This study is kind studies using action research or (PTK) is conducted in two cycles. Each cycle consists of planning, action planning, observation / evaluation and reflection. Subject empirically n are children aged 4-5 years are numbered 15 children in early childhood Darussalam , The research data obtained through observation and data analysis was done by using quantitative descriptive analysis. The research shows that the weaving activity can improve fine motor skills in children aged 4-5 year. It can be seen from the increase in the average percentage of fine motor skills in the first cycle of 56.33%, which is the category of pretty and an increase of 36.68% in the second cycle be 76.99% which are in both categories. So, weaving activities can improve fine motor skills children aged 4-5 years in early childhood Darussalam Petapahan Jaya Village District Tapung Regency KamparKeywords : Fine Motor Skill, Weaving Activity With Colored Paper